PENDIDIKAN TRANSAKSIONAL SEBAGAI MODEL INTERAKSI: KAJIAN INTERDISIPLINER PENDIDIKAN DAN HUKUM - Angga Galucci; Muhlis Muhlis; Muhammad Aulia Rahman (STKIP Subang, 2026)
This study aims to analyze transactional education as an interaction model between teachers and students from both pedagogical and juridical perspectives. Transactional education is understood as a reciprocal communication process that emphasizes active participation from both parties. The research method employed a qualitative approach with a case study in secondary schools, using observation, interviews, and documentation. The findings reveal that transactional education fosters a democratic learning atmosphere, enhances student motivation, and strengthens teacher-student relationships. Nevertheless, its implementation faces challenges such as differences in student characteristics and power dynamics within the classroom. From a juridical standpoint, transactional education has clear legal legitimacy through Law No. 20 of 2003 on the National Education System and Law No. 14 of 2005 on Teachers and Lecturers. These regulations affirm students’ rights to actively participate and teachers’ obligations to conduct professional and ethical teaching. Therefore, transactional education can be regarded as an interaction model that is pedagogically relevant and legally valid.